2021
DOI: 10.46606/eajess2021v02i01.0069
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Strategic Planning and Academic Performance among the Public Secondary Schools in Babati District, Tanzania

Abstract: This study sought to establish teachers’ perception on the schools’ effectiveness in the development of the strategic plan, the perception of teachers on how the implementation of the strategic plan affects the academic performance and what should be done to ensure an effective strategic planning. The study used a mixed research approach while employing the convergent parallel design. The study population consisted of 2,844 stakeholders from 5 sampled schools whereby 185 respondents were drawn. The study conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…The observed findings support the findings by Kwaslema and Onyango [26] who observed a positive contribution of strategic implementation practices towards improved academic performance among public secondary school students in Babati district. Moreover, Meigaru et al [20] established that, strategic planning implementation practices has a positive influence on students' academic performance.…”
Section: The Influence Of Strategic Implementation Practices On Stude...supporting
confidence: 89%
See 3 more Smart Citations
“…The observed findings support the findings by Kwaslema and Onyango [26] who observed a positive contribution of strategic implementation practices towards improved academic performance among public secondary school students in Babati district. Moreover, Meigaru et al [20] established that, strategic planning implementation practices has a positive influence on students' academic performance.…”
Section: The Influence Of Strategic Implementation Practices On Stude...supporting
confidence: 89%
“…This finding supports the empirical work by Meigaru et al [20] who observed that, involvement of tutors in setting goals and operational activities made it easier to scale up and improve students' academic performance in public teacher colleges in Tanzania. Likewise, Kwaslema and Onyango [26] revealed that, strategic implementation practices in terms of teachers' involvement in determination of short-term plans and school activities contributed to enhanced motivation among the school community to work hard as a team and eventually improved students' performance [51]. Furthermore, the above findings were also supported by evidence gleaned from documentary review analysis whose results revealed that, the adoption of strategic implementation practices in the school development planning process had significant influence on students' academic performance.…”
Section: The Influence Of Strategic Implementation Practices On Stude...mentioning
confidence: 98%
See 2 more Smart Citations
“…The SEM test found that the relationship between the implementation of the organizational strategic plan and the school's academic achievement was significant at a positive value. The study gave the same findings as Agi (2017); Al-Mawdieh (2020); Ameen (2019); Caputo and Rastelli (2014); Kasan (2013); Ebiziem et al (2021); Ford and Ihrke (2019); Kwaslema and Onyango (2021); Meigaru et al (2019); Meyers and VanGronigen (2019); Meyers and Hitt (2018); Mintrop and MacLellan (2002); Russell and Sharpe (2014); Strunk et al (2016); Waters and Marzano (2006) found that school academic excellence is achieved when the organizational strategic plan is implemented effectively. This is also supported by Bryson et al (2018); Wolf and Floyd (2017); Zakayo (2018) who explained that the organizational strategic plan influences and has a positive impact on school academic achievement.…”
Section: The Relationship Between the Implementation Of Organizationa...supporting
confidence: 68%